A Half-Discrete Hilbert-Type Inequality in the Whole Plane with Multiparameters. (7th September 2016) - Ma, Qunwei; Yang, Bicheng; He, Leping
Abstract : By the use of weight functions and technique of real analysis, a new half-discrete Hilbert-type inequality in the whole plane with multiparameters and the best possible constant factor is given. Furthermore, the equivalent forms, two kinds of particular inequalities, and the operator expressions with the norm are considered.